2018
DOI: 10.3892/mmr.2018.9607
|View full text |Cite
|
Sign up to set email alerts
|

Apelin‑13 ameliorates metabolic and cardiovascular disorders in a rat model of type 2 diabetes with a high‑fat diet

Abstract: Apelin has been reported to be associated with multiple physiological processes in the cardiovascular system. The aim of the present study was to investigate the effects of Apelin-13 administration on cardiac function, hyperglycemia, insulin resistance (IR), dyslipidemia, endothelial function, inflammation and glucose metabolism in type 2 diabetic Goto-Kakizaki (GK) rats, and compare the protective effects of Apelin-13 with metformin or atorvastatin. In the present study, type 2 diabetes was induced in male Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Additionally, TC and TG are predictors of the balance of lipid metabolism, while a previous study also noted that individuals with high TC/HDL-C or LDL-C/HDL-C ratios had greater cardiovascular risk [28] because these ratios reflected the balance between transport of cholesterol to peripheral tissues and reverse transport to the liver. Furthermore, a recent study in a rat model showed that apelin improved dyslipidaemia by decreasing TC, TG and LDL-C, and increasing HDL-C concentration [29]. Overall, our findings in Thai children suggest that apelin might provide an inverse association with cardiometabolic risks.…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, TC and TG are predictors of the balance of lipid metabolism, while a previous study also noted that individuals with high TC/HDL-C or LDL-C/HDL-C ratios had greater cardiovascular risk [28] because these ratios reflected the balance between transport of cholesterol to peripheral tissues and reverse transport to the liver. Furthermore, a recent study in a rat model showed that apelin improved dyslipidaemia by decreasing TC, TG and LDL-C, and increasing HDL-C concentration [29]. Overall, our findings in Thai children suggest that apelin might provide an inverse association with cardiometabolic risks.…”
Section: Discussionsupporting
confidence: 69%
“…However, some authors have reported proinflammatory action of APLN [104]: in a clinical study performed by Heinonen et al patients with metabolic syndrome showed high level of APLN and TNF-α [105] while other studies revealed that APLN mitigates hepatic macrophage infiltration and TNF-α expression and reduces myocardial inflammation induced by diabetes condition or sepsis shock [106][107][108][109].…”
Section: Apelin/apj Axis: Biological Rolementioning
confidence: 99%
“…apelin-13 (200 µg/kg bw for 4 weeks) on cardiac function and metabolic status have also been observed in obese diabetic Goto-Kakizaki (GK) rats (T2DM model). 79 Such benefits may be linked to apelin-induced sphingosine kinase 1 mediated inhibition of transforming growth factor beta (TGF-β). 80 Thus, TGF-β is a proinflammatory cytokine that is upregulated in diabetes 81 and induces cardiac fibrosis alongside extra cellular matrix protein deposition, 82 representing key risk factors in cardiac hypertrophy.…”
Section: Diabetic Complicationsmentioning
confidence: 99%